Implementation of the One Week One Juz Method as an Effort to Improve Students' Al-Qur'an Reading Skills at MIN 2 Wonogiri - Sundari, Evi Dyah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to investigate the implementation of the One Week One Juz (OWOJ) method as an effort to improve students' Al-Qur'an reading skills at MIN 2 Wonogiri. The method, which encourages students to read one Juz (part) of the Al-Qur'an every week, is designed to enhance their fluency, comprehension, and memorization of the Qur'anic verses. This research utilizes a classroom action research (CAR) approach, involving a series of cycles that include planning, action, observation, and reflection. The subjects of the study are students of Grade 6 at MIN 2 Wonogiri, who are assessed through pre-test and post-test evaluations, as well as ongoing observation of their progress. Data are collected through qualitative methods, including interviews, classroom observations, and field notes, as well as quantitative methods such as test scores. The results of the study indicate that the implementation of the OWOJ method significantly improved students' Al-Qur'an reading skills, including fluency, pronunciation, and understanding of the verses. Additionally, the method fostered a greater sense of discipline and spiritual connection among the students, as they became more motivated to engage with the Qur'an regularly. This study concludes that the One Week One Juz method can be an effective approach to enhance Al-Qur'an literacy among students in primary schools, contributing to their religious and academic development. The research provides valuable insights for educators looking to integrate structured Qur'anic reading practices into their teaching strategies.